Analisis Strategi Pemasaran Lembaga Pendidikan Islam: Studi di Madrasah Aliyah Sabilul Muttaqin Mojokerto - Fiki Amaliatul Ilmi; M. Saipuddin Zuhri; Reni Puspita Yanti (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
The effective execution of marketing tactics can aid in the recruitment of prospective students and concurrently elevate the standing of the madrasa. This research aims to analyze the marketing strategy at MA Sabilul Muttaqin in Pungging part of Mojokerto. Case study method was used where five participants were interviewed from that madrasa. Interviews were conducted with using a semi-structured interview method with open-ended questions related to branding strategies. This study concludes that marketing strategy of madrasa in marketing of Islamic educational institutions is to use a socio-religious, artistic and cultural approach through madrasa education programs. Beside it, concept of integration of Sabilul Muttaqin Islamic Boarding School curriculum is a combination or combination of cottage and madrasah materials simultaneously and continuously.